TRIBAL WOMEN IN MILLET-BASED ENTREPRENEURSHIP: A GLIMPSE OF ODISHA - Pandey, Bhawna; Yadav, Dhanwati; Anand, Nitish; Suman, Bhavna; Co-Pi; Singh, Dyal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research text studies the dynamics of millet-based entrepreneurship among tribal women in Odisha, India, with a key focus on possibilities, barriers, and policy effectiveness. The study adopts a descriptive empirical technique that relies on secondary data analysis and policy assessment. The findings state, whereas tribal women account for almost most of the total millet-growing farmers, they face major challenges to turning their agricultural engagement into successful business endeavours. The study assesses different policy instruments, including the Odisha Millets Mission, which offers targeted assistance through initiatives. It has open up potential entrepreneurship opportunities across the millet value chain, implementation gaps still remain, with only limited number of eligible women receiving benefits owing to barriers. The study indicates that, despite the expanding market potential for millet-based businesses, institutional and societal restrictions continue to impede indigenous women’s economic growth. The recommendations emphasise the need for enhanced policy implementation mechanisms and comprehensive support systems to ensure an ascending quality engagement of women in the millet value chain.